2019
DOI: 10.1097/sla.0000000000003400
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Acute Pain After Surgery

Abstract: Objectives: To identify perioperative practice patterns that predictably impact postoperative pain. Background: Despite significant advances in perioperative medicine, a significant portion of patients still experience severe pain after major surgery. Postoperative pain is associated with serious adverse outcomes that are costly to patients and society. Methods: The presented analysis took advantage of a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
1
20
1
1
Order By: Relevance
“…For tonsillectomies, an interesting result not previously reported for children was the use of different classes of non-opioid analgesics given as a preventive dose, which seemed to improve patient-reported outcome. 11 Not receiving a preventive non-opioid analgesic was associated with an increased desire for more pain medication, higher opioid doses, more adverse events, and more pain-related interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For tonsillectomies, an interesting result not previously reported for children was the use of different classes of non-opioid analgesics given as a preventive dose, which seemed to improve patient-reported outcome. 11 Not receiving a preventive non-opioid analgesic was associated with an increased desire for more pain medication, higher opioid doses, more adverse events, and more pain-related interference.…”
Section: Discussionmentioning
confidence: 99%
“…18e21 A study in adults showed a dose-dependent association between the preventive use of non-opioid analgesics and postoperative pain scores, a finding which could be confirmed in our tonsillectomy group. 11 Some previous trials underlined that the addition of paracetamol to an NSAID did not always improve analgesia compared with an NSAID alone. 18e21 For metamizole, data on efficacy are scarce, specifically on the combinations with other non-opioid classes, as it is not marketed in all countries.…”
Section: Desire For More Pain Treatmentmentioning
confidence: 99%
“…Ein eventueller Vorteil einer prä- und intraoperativen Gabe mehrerer NOPA unterschiedlicher Substanzgruppen wurde bis jetzt kaum systematisch untersucht, obwohl dieses Vorgehen in der klinischen Praxis weit verbreitet ist [ 70 ]. Aktuelle Registerdaten von über 1000 Patienten nach Rückenoperationen bestätigten eine bessere Analgesie bei intraoperativer Gabe von zwei oder sogar drei NOPA verschiedener Substanzgruppen (NSAID, Metamizol, Paracetamol) im Vergleich zu keinem oder nur einem NOPA [ 7 ]. Auch bei Kindern nach Tonsillektomien und Appendektomien war die intraoperative Gabe von mindestens zwei NOPA mit weniger Wunsch nach Schmerzmitteln für die ersten 24 h postoperativ assoziiert im Vergleich zu keinem oder einem NOPA [ 84 ].…”
Section: Allgemeine Empfehlungenunclassified
“…Although laparoscopic surgery has advantages such as enhanced postoperative recovery and decreased hospital stay in comparison with open surgery [ 1 , 2 ], the incidence of moderate-to-severe acute postoperative pain, especially in the recovery room, remains up to 70% [ 3 , 4 ]. Moreover, pain intensities vary even after the same surgery, which suggests the need for individual evaluation of risk factors for postoperative pain [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%